Los alumnos más capaces en España. Normativa e incidencia en el diagnóstico y la educación - Jimenez Fernández, Carmen; García Perales, Ramón (REOP - Revista Española de Orientación y Psicopedagogía, 2014)
RESUMEN El presente estudio analiza la regulación nacional y regional sobre la educación de los más capaces Se concluye que la LOGSE (1990), que impulsó la atención a la diversidad, omitió toda referencia a estos alumnos, situación que corregiría parcialmente en sus desarrollos normativos posteriores. Las Comunidades Autónomas han regulado el tema de forma desigual y se refleja en la diversidad de procesos de diagnóstico y respuesta educativa existentes. En la educación primaria se diagnostican 1,3 veces más alumnos que en la secundaria obligatoria y seis veces más que en bachillerato. Existen en similar proporción en los centros públicos y privados-concertados siendo la media nacional de alumnos diagnosticados con alta capacidad del 0,08%, proporción raquítica para los parámetros habituales en el desarrollo del talento y la educación excelente. Dos tercios de los identificados son varones, preponderancia que parece ligada a estereotipos de género pues no se da entre los alumnos con rendimiento excelente en los estudios PISA (2006, 2009), ni en los alumnos con Premio Extraordinario de Bachillerato o Beca de Excelencia (Jiménez et al., 2006, 2010). ABSTRACT The study analyses the national and regional (Autonomous Communities, AC) regulations for the education of highly gifted students, and the impact on their identification and educative intervention. We conclude that the LOGSE (General Organic Regulation of the Education System in Spain, 1990), which prompted the attention to diversity, failed to mention these students, though this situation was partially modified in subsequent developments of the law. The AC have regulated this issue differently, which is seen in the diversity of processes of diagnosis used, and the types of attention given to the learning needs of these students, as well as in the proportion of identified students found within these programs. We come across that there is 1.3 times more students identified in primary schools programs than in secondary, and six times more than in high school. Proportions are similar both in public and state-subsidized schools. The national average for high ability students is 0.8%, a paltry proportion in the context of usual parameters on development of talent and excellent and equitable education for all students. Two thirds of the identified students are male, and this preponderance seems to be linked to gender stereotypes, because it is not found among students with excellent performance from PISA studies (2006, 2009) , nor among students with High School Awards or with Excellence scholarships (Jimenez et al., 2006, 2010).